Self‐Healing Silk Fibroin‐Based Hydrogel for Bone Regeneration: Dynamic Metal‐Ligand Self‐Assembly Approach. (2nd August 2017) - Shi, Liyang; Wang, Fanlu; Zhu, Wei; Xu, Zongpu; Fuchs, Sabine; Hilborn, Jöns; Zhu, Liangjun; Ma, Qi; Wang, Yingjie; Weng, Xisheng; Ossipov, Dmitri A.
Abstract : Despite advances in the development of silk fibroin (SF)‐based hydrogels, current methods for SF gelation show significant limitations such as lack of reversible crosslinking, use of nonphysiological conditions, and difficulties in controlling gelation time. In the present study, a strategy based on dynamic metal‐ligand coordination chemistry is developed to assemble SF‐based hydrogel under physiological conditions between SF microfibers (mSF) and a polysaccharide binder. The presented SF‐based hydrogel exhibits shear‐thinning and autonomous self‐healing properties, thereby enabling the filling of irregularly shaped tissue defects without gel fragmentation. A biomineralization approach is used to generate calcium phosphate‐coated mSF, which is chelated by bisphosphonate ligands of the binder to form reversible crosslinkages. Robust dually crosslinked (DC) hydrogel is obtained through photopolymerization of acrylamide groups of the binder. DC SF‐based hydrogel supports stem cell proliferation in vitro and accelerates bone regeneration in cranial critical size defects without any additional morphogenes delivered. The developed self‐healing and photopolymerizable SF‐based hydrogel possesses significant potential for bone regeneration application with the advantages of injectability and fit‐to‐shape molding. Abstract : Reversible coordination bonds are employed to achieve self‐assembly of novel silk fibroin hydrogel that flows on applied stress, rapidly self‐heal after injection, and is subsequently photopolymerized. Using silk microfibers as templates for biomineralization and a natural biopolymer binder provides hierarchical structure of the network. Implantation of the hydrogel into rat cranial critical size defect facilitates bone regeneration without exogenous growth factors.